Le web social – La complexité au service de l'apprentissage informel de l'anglais - Geoffrey Sockett (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article presents the results of a research project using blogs written by trainee language teachers to report on their informal online social networking activities in English. The respondents, who are trained in areas such as language acquisition theories, are invited to discuss how they might be learning English through these activities. The resulting corpus of blogs is analysed and the impact of these activities on learning of the target language is discussed. The theoretical framework for this study is dynamic systems theory, and it is argued that this model is particularly pertinent for the description of language learning in an informal online context. The results of the study suggest that the very large number of interactions between people, media, languages and social networking interfaces leads to non-linear language development, and phase transitions are observed in fluency and vocabulary acquisition. Suggested applications include the use of informal learning blogs as a pedagogical tool to allow learners to see their informal activities as valuable for language learning and avenues for further research are suggested.